Diagnosis and management of type 2 diabetes mellitus in patients with ischaemic heart disease and acute coronary syndromes - a review of evidence and recommendations - Shah, Muhammad Usman; Roebuck, Alun; Srinivasan, Bala; Ward, Joanna Kate; Squires, Paul Edward; Hills, Claire Elizabeth; Lee, Kelvin (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus (T2DM) represents a major healthcare condition of the 21st century. It is characterised by persistently elevated blood glucose occurring as a result of peripheral insulin resistance and reduced insulin production which may lead to multiple long-term health conditions such as retinopathy, neuropathy, and nephropathy. The estimated number of individuals suffering from diabetes mellitus (DM) is expected to rise to 591 million by the year 2035 with 4.4 million in the United Kingdom (UK) alone, 90% of which is attributed to T2DM. Moreover, a significant proportion of individuals may have undetected diabetes mellitus, especially among those presenting with symptoms of ischaemic heart disease (IHD). This is particularly important in those individuals presenting with acute coronary syndromes (ACS) who are at the highest risk of complications and sudden cardiac death. Identifying abnormal levels of common biochemical markers of diabetes, such as capillary blood glucose or glycated haemoglobin (HbA1c) in these patients is important for early diagnosis, which will then allow for timely intervention to improve outcomes. However, a significant proportion of individuals who meet the criteria for the diagnosis of diabetes remain undiagnosed, representing missed opportunities for early intervention. This may result in a prolonged period of untreated hyperglycaemia, which can result resulting in significant further microvascular and macrovascular complications. There is an increased risk of IHD, heart failure, cerebrovascular accidents (CVA), and peripheral artery disease (PVD). These account accounting for 50% of deaths in patients with T2DM. Cardiovascular diseases in the context of diabetes particular represent a significant cause of morbidity and mortality with a two to three times higher risk of cardiovascular disease in individuals with T2DM than in those without the condition normo-glycaemia. In the United Kingdom UK alone, around 120 amputations, 770 CVA, 590 heart attacks, and more than 2300 presentations with heart failure per week are attributed to diabetes DM. with One 1 in six 6 hospital beds and around 10% of the healthcare budget may be being spent on managing diabetes DM or its complications. Therefore, it represents a significant burden on our healthcare system.